Trust Formation across Academic Disciplines: The Role of Thought Styles in Interpreting Leadership Behaviors - Suacamram, Mayuree; Luo, Qiuxue (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study examines how disciplinary thought styles influence trust formation in Humanities and Social Sciences (HSS) collaborations. The objective of this study is to explain how disciplinary cognition shapes the interpretation of leadership behaviors and to test whether modeling discipline as a cognitive filter improves predictive accuracy. We develop a framework that treats thought styles as cognitive filters that shape how leadership behaviors are interpreted as trust signals across different academic disciplines. The approach measures thought styles through psychometric scales and models their filtering effects on multimodal behavioral signals using path analysis with multigroup structural equation modeling. The research adopts a quantitative design based on multimodal behavioral data and survey measures, with purposive sampling of interdisciplinary research teams. An empirical study with 42 research teams (History and Sociology) demonstrates that identical leadership behaviors elicit different trust perceptions across disciplines, with historians responding more to contextual detail and temporal framing, while sociologists prioritize theoretical integration and methodological transparency. The framework shows improved predictive accuracy compared to models treating disciplines as simple covariates. The proposed model showed good fit (χ²/df = 1.32, CFI = 0.96, RMSEA = 0.04, SRMR = 0.05) compared to baseline (χ²/df = 2.81, CFI = 0.82) and covariate models (χ²/df = 2.15, CFI = 0.88). These results confirm that disciplinary thought styles function as active filtering mechanisms that systematically condition trust formation and team effectiveness. These findings suggest that accounting for disciplinary cognitive diversity may enhance our understanding of trust dynamics in interdisciplinary academic collaborations.